SOSIALISASI PENGGUNAAN MICROSOFT WORD DALAM PEMBUATAN MAKALAH PADA SISWA/I PESANTREN BAHRUL HADI ARRAHMANI - Abdul Azis Salim; Alexsandro Deldiero; Arif Wibawa; Cut Fatma Anwar; Fazriel Arief Nugraha; Mahsa Nurfarhan Hidayat; Muhammad Atlant Modestio; Muhammad Ghozy; Teguh Zakaria (Abdi Jurnal Publikasi, 2022)
Microsoft Office is a software that is much needed in today’s digital era. In Microsoft Office software there are many applications provided by Microsoft, such as Microsoft Word, Microsoft Excel, Microsoft Power Point, and Microsoft Outlook. Microsoft Word is a software that functions to process words. Microsoft Word was first published in 1983 under the name Multi-Tool Word for Xenix. With the development of today’s digital era, many people in the office, health and education sectors need the Microsoft Word applications to create a document. Therefore a socialization activity was created to use Microsoft Word in the framework of Community Service, this activity aims to increase the understanding of students and female students at the Bahrul Hadi Arrahmani Islamic Boarding School in making a paper using Microsoft Word software. After carrying out the activities of delivering material and practicing, the students and female students at the Bahrul Hadi Arrahmani Islasmic Boarding School can understand making papers using Microsoft Word. This socialization activity aims to increase knowledge and insight for students and female students in using the Microsoft Word applications.